2013
DOI: 10.1016/j.ajpath.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Activated Alveolar Epithelial Cells Initiate Fibrosis through Secretion of Mesenchymal Proteins

Abstract: Fibrosis is characterized by accumulation of activated fibroblasts and pathological deposition of fibrillar collagens. Activated fibroblasts overexpress matrix proteins and release factors that promote further recruitment of activated fibroblasts, leading to progressive fibrosis. The contribution of epithelial cells to this process remains unknown. Epithelium-directed injury may lead to activation of epithelial cells with phenotypes and functions similar to activated fibroblasts. Prior reports that used a repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 65 publications
8
86
0
Order By: Relevance
“…The increased release of collagen into the medium due to TNF-a stimulation could underlie the increased collagen content in both alveolar and small airway walls of SPC-TNF-a mice, as well as in patients with COPD, as we recently published (3,4). Evidence for the involvement of epithelial cells in fibrotic processes is also demonstrated by other work, which shows limitation of bleomycin-induced fibrosis in epithelial-specific collagen I knockout mice (5). Furthermore, because MMP2 and MMP9 expression increased after TNF-a stimulation of epithelial cells, and because MMPs were recently associated with the breakdown of elastin in SPC-TNF-a mice and patients with COPD, TNF-a could possibly contribute to the reported degradation of elastin (3,23).…”
Section: Discussionsupporting
confidence: 50%
“…The increased release of collagen into the medium due to TNF-a stimulation could underlie the increased collagen content in both alveolar and small airway walls of SPC-TNF-a mice, as well as in patients with COPD, as we recently published (3,4). Evidence for the involvement of epithelial cells in fibrotic processes is also demonstrated by other work, which shows limitation of bleomycin-induced fibrosis in epithelial-specific collagen I knockout mice (5). Furthermore, because MMP2 and MMP9 expression increased after TNF-a stimulation of epithelial cells, and because MMPs were recently associated with the breakdown of elastin in SPC-TNF-a mice and patients with COPD, TNF-a could possibly contribute to the reported degradation of elastin (3,23).…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, ECM secreted by lung fibroblasts from older animals further drove myofibroblast differentiation of fibrocytes in vitro [278]. Importantly, recent findings suggest that next to mesenchymal cells other structural cells, such as alveolar epithelial or circulating (progenitor) cells, contribute to ECM production [279][280]. All these cell types potentially exhibit age-related cell-autonomous alterations, as described earlier.…”
Section: Altered Intercellular Communicationmentioning
confidence: 83%
“…Deletion of type I collagen within lung epithelial cells led to attenuation of lung fibrosis (57). In the present study, we found an important role for epithelial-derived CTGF for activation of fibroblasts and epithelial cells and for lung fibrogenesis.…”
mentioning
confidence: 84%